DIGITAL TRANSACTIONS IN CULTURAL AND VISUAL ART SPACES AUDIENCE INTENTIONS AND LOYALTY TOWARD FINTECH PAYMENT PLATFORMS IN DELHI NCR - Vij, Simran; Pandoi, Deepika (ShodhKosh: Journal of Visual and Performing Arts, 2025)
With the fast adoption of fintech payment systems, fintech has changed transactional relationships in cultural and visual art spaces, but the empirical study on audience intention and loyalty in the experience setting is not highly researched. This paper will look at the drivers of audience intention and loyalty to the fintech payment systems in cultural and visual art venues in the Delhi National Capital Region (NCR). Based on Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology, Trust Theory, and Relationship Marketing Theory, a conceptual framework was formulated and empirically verified with the help of survey data, processed with the help of Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived usefulness, perceived ease of use, perceived security, and trust play a key role in the intention of the audience to use fintech payment platforms. The intention to the audience has a positive influence on satisfaction, and consequently, a central mediator of loyalty to fintech platforms. The findings indicate that the fintech adoption is fundamentally shifted towards trust and experience satisfaction that drives it to audience engagement in the cultural and visual art world. The project builds on existing studies on fintech adoption in cultural economies and offers applicable findings to cultural bodies, fintech services infrastructure, and the policy community on how to enhance digital payment infrastructures and customer retention in the creative industries.